Normal-pressure tests of rectangular plates - Ramberg, Walter (U.S. Government Printing Office, 1942)
Normal-pressure tests were made of 56 rectangular plates with clamped edges and of 5 plates with freely supported edges. Pressure was applied and the center deflection and the permanent set at the center wer measured. For some of the plates, strains and contours were measured in addition.